rethorical tropes utilized in cnn indonesia online news - ika maratus sholikhah (Faculty of Humanities, Universitas Jenderal Soedirman, 2017)
This research is aimed at analyzing the use of rhetoric in national online news. Rhetoric is an effective and persuasive speaking or writing. Rhetoric frequently uses exaggerative even bombastic language. The purpose of rhetoric is to obtain particular effect as well as persuade the readers. In online news, rhetoric is used to persuade economically and ideologically. Economically, online news is a market commodity that must be promoted. Ideologically, online news is a domination of institution or others. These purposes influence the language employed in the online media or news online. To gain the objectives, researcher applied descriptive qualitative research. The data were collected from 15 news articles published in CNN Indonesia online news on March 2017. Then, the data were analyzed based on the objective of the study. After compiling the data, the researcher classified rhetorical tropes and news structure in CNN Indonesia. The result shows four types of rhetorical tropes utilized in online news, they are: hyperbole, metonym, metaphor, and neologism. Furthermore, the news structures in CNN Indonesia emphasize on three strategies: providing information that also has an attitudinal and emotional dimension, building strong relational structure for facts, and emphasizing the factual nature of events.